Intraoperative Management of Hypercapnia With an Extracorporeal Carbon Dioxide Removal Device During Giant Bullectomy. Issue 2 (March 2016) - Dell'Amore, Andrea; D'Andrea, Rocco; Caroli, Guido; Mazzoli, Carlo Alberto; Rocca, Alberto; Stella, Franco; Bini, Alessandro; Melotti, Rita
Abstract : Abstract: Extracorporeal CO2 -removal devices have been introduced in clinical practice to provide protective and ultraprotective ventilation strategies in different settings to avoid retention of carbon dioxide. The need to facilitate lung-protective ventilation is required not only for the treatment of acute respiratory distress syndrome but also in thoracic surgery during complex operations, especially in respiratory compromised patients. This report describes a case of giant bullectomy for vanishing lung syndrome in which intraoperative hypercapnia secondary to protective ventilation was managed with a CO2 -removal device (Decap-Hemodec s.r.l., Salerno, Italy). To the best of our knowledge, this is the first report in the literature of the intraoperative use of the Decap system for giant bullectomy.